Role of individual and organizational variables as predictors of job satisfaction among hotel employees - Viseu, J. (2021)
Job satisfaction is a key concept in the organizational literature, as satisfied employees allow organizations to achieve desired work-related outcomes. Nevertheless, more research is needed to understand what organizational and individual variables shape the job satisfaction of employees from the hospitality sector. This study assesses the role of organizational variables (perceived organizational support and organizational health) and individual variables (positive psychological capital and creative personality) as possible determinants of job satisfaction. A total of 504 hotel employees from the Algarve region, the main Portuguese tourism destination, participated in this study. Structural equation modeling with latent variables was used to evaluate the proposed model. Results showed that perceived organizational support was the most important predictor of job satisfaction, followed by organizational health. Organizational health also predicted positive psychological capital, which, in turn, was significantly associated with job satisfaction. These results have important practical implications for human resources management in the hospitality industry.